1973
DOI: 10.1902/jop.1973.44.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Gingival Fibromatosis, Hypertelorism, Anti‐Mongoloid Obliquity, Multiple Telangiectases and Cafe Au Lait Pigmentation; A Unique Combination of Developmental Anomalies

Abstract: DIFFUSE, IDIOPATHIC GINGIVAL ENLARGEMENT is knownby various terms: gingival fibromatosis, fibromatosis gingivae, diffuse gingival hyperplasia, hypertrophy of the gums, idiopathic gingival hyperplasia, elephantiasis gin givae, gigantism of the gingivae, hereditary gingival fibromatosis, multiple epulides, hypertrophic gingivae, and congenital macrogingivae. We will use the term gingival fibromatosis in keeping with a recent and ex cellent review of this subject. 1The most common conditions which could be con fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1976
1976
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…1 Gingival fibromatosis may also be observed together with a wide variety of genetically inherited disorders, such as cherubism, hypertrichosis, sensorineural hearing loss, Laband syndrome, Ramon syndrome associated with juvenile rheumatoid arthritis, Klippel-Trenaunay-Weber syndrome, and psychomotor retardation. [2][3][4][5][6][7][8][9] In addition to these systemic conditions, HGF has also been reported to occur with other intraoral/dental pathologies, such as supernumerary teeth 10 and histopathologic premalignancy characterized with epithelial dysplasia. 11 Isolated (non-syndromic) HGF can be caused by mutation of the SOS1 gene, 12 but the existence of genetic heterogeneity for HGF indicates that mutations of other genes can also cause the condition.…”
Section: Introductionmentioning
confidence: 99%
“…1 Gingival fibromatosis may also be observed together with a wide variety of genetically inherited disorders, such as cherubism, hypertrichosis, sensorineural hearing loss, Laband syndrome, Ramon syndrome associated with juvenile rheumatoid arthritis, Klippel-Trenaunay-Weber syndrome, and psychomotor retardation. [2][3][4][5][6][7][8][9] In addition to these systemic conditions, HGF has also been reported to occur with other intraoral/dental pathologies, such as supernumerary teeth 10 and histopathologic premalignancy characterized with epithelial dysplasia. 11 Isolated (non-syndromic) HGF can be caused by mutation of the SOS1 gene, 12 but the existence of genetic heterogeneity for HGF indicates that mutations of other genes can also cause the condition.…”
Section: Introductionmentioning
confidence: 99%
“…However, several ZLS-related entities have been reported to include caf e-au-lait pigmentation [Giansanti et al, 1973] or hypopigmentation [Tezcan et al, 1997]. The finding of segmental hyperpigmentation/hyperplasia in our proband suggests mosaicism for the gene defect causing ZLS; or perhaps a microdeletion with haploinsufficiency for neighboring genes explaining thus the extended phenotype.…”
Section: Table I Clinical Characteristics In the Present Patient Andmentioning
confidence: 55%
“…Literature review showed that the main features of the syndrome are gingival hypertrophy associated with nails or terminal phalanges hypo/aplasia (100% of patients). [43][44][45][46][47][48][49][50] In more than 50% of the patients, a typical facial appearance is detectable, characterized by thick ears, large and bulbous nose, and thick lips with or without macrostomia. Common reported clinical features are moreover ID (more than 40%), joints hypermobility (48%), hypertrichosis of the face and/or the body (37%), hepatosplenomegaly (27%), and seizures (13%).…”
Section: Zimmermann-laband Syndromementioning
confidence: 99%
“…50 Clinical variability is wide even in the same family, and, as commonly observed, the seriousness of the somatic involvement often does not correlate with the severity of the ID. Several other rarer signs have been reported, as pigmentation disorders, 43,49 supernumerary teeth, 45,46,49 ocular anomalies, 47,49 and others. 44,48,49 This wide spectrum of clinical presentations of ZLS reported in the literature could be partly due to the absence, to date, of any confirmatory diagnostic test aimed at clearly defining the ZLS phenotype as compared with the overlapping conditions (DOOR and Cantù syndromes).…”
Section: Zimmermann-laband Syndromementioning
confidence: 99%